2019
DOI: 10.3389/fphar.2019.00672
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study About the Relationship Between CEUS of Carotid Intraplaque Neovascularization and Ischemic Stroke in TIA Patients

Abstract: Objective: To evaluate the relationship between contrast-enhanced ultrasonography (CEUS) of carotid intraplaque neovascularization and ischemic stroke in transient ischemic attack (TIA) patients. Methods: A total of 112 TIA patients were selected for the study. Routine carotid ultrasonic examination was performed for all the patients. CEUS was carried out for consecutive patients with plaque thicker than 2.5 mm in carotid bifurcation and follow-up for at least 24 months. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…30,31 Furthermore, our findings suggested that carotid IPN identified in SMI is highly correlated to the evaluation of pathology. Previous studies have indicated IPN highly associated with ischemic stroke in TIA patients, 32 our findings also demonstrated patients with IPN detected by SMI more likely to be exposed to stroke or TIA. Our data supports the diagnostic efficacy of SMI in the detection of IPN.…”
Section: Discussionsupporting
confidence: 83%
“…30,31 Furthermore, our findings suggested that carotid IPN identified in SMI is highly correlated to the evaluation of pathology. Previous studies have indicated IPN highly associated with ischemic stroke in TIA patients, 32 our findings also demonstrated patients with IPN detected by SMI more likely to be exposed to stroke or TIA. Our data supports the diagnostic efficacy of SMI in the detection of IPN.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies reported that the echogenicity of the plaques was negatively correlated with the plaque neovascularization grades. Therefore, CEUS examination should be performed in patients with carotid plaques that are hypoechoic (types I and II) ( Staub et al, 2011 ; Li et al, 2019 ). Thus, assessing plaque vulnerability is a cost-effective risk stratification method in patients with asymptomatic carotid stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast-enhanced ultrasound (CEUS) is used to examine plaque vulnerability by visualizing intraplaque neovessels in real time. According to studies of symptomatic carotid stenosis patients, IPN assessment using CEUS is independently associated with an increased risk of ischemic stroke after adjusting for the degree of stenosis ( Li et al, 2019 ; Camps-Renom et al, 2020 ; Song et al, 2020 ). In addition, it may serve as a clinically useful tool for cardiovascular risk stratification in patients with coronary events ( Nakamura et al, 2015 ; Mantella et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The degree of enhancement of intraplaque neovascularisation is related to cardiovascular and cerebrovascular events. [10][11][12] Some studies reported that intraplaque neovascularisation assessed by CEUS correlates significantly with histopathological findings of the same lesions. Moreover, the enhancement of intraplaque neovascularisation, which was assessed using CEUS, was consistent with the density of plaque neovascularisation, which was detected by immunohistochemistry, in patients with severe carotid stenosis undergoing endarterectomy.…”
Section: Introductionmentioning
confidence: 99%